2018
DOI: 10.1073/pnas.1722619115
|View full text |Cite
|
Sign up to set email alerts
|

Cell contraction induces long-ranged stress stiffening in the extracellular matrix

Abstract: Animal cells in tissues are supported by biopolymer matrices, which typically exhibit highly nonlinear mechanical properties. While the linear elasticity of the matrix can significantly impact cell mechanics and functionality, it remains largely unknown how cells, in turn, affect the nonlinear mechanics of their surrounding matrix. Here, we show that living contractile cells are able to generate a massive stiffness gradient in three distinct 3D extracellular matrix model systems: collagen, fibrin, and Matrigel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
218
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(238 citation statements)
references
References 57 publications
16
218
4
Order By: Relevance
“…al. (34) indeed demonstrated that stiffness becomes anisotropic near contracting cells, with a higher extent of stiffening in the radial relative to the angular direction. Moreover, in our simulations, radially aligned fibers are stretched, whereas angularly aligned fibers are typically compressed (Fig.…”
Section: Strain-induced Elastic Anisotropy: Effects Of Fiber Alignmenmentioning
confidence: 85%
“…al. (34) indeed demonstrated that stiffness becomes anisotropic near contracting cells, with a higher extent of stiffening in the radial relative to the angular direction. Moreover, in our simulations, radially aligned fibers are stretched, whereas angularly aligned fibers are typically compressed (Fig.…”
Section: Strain-induced Elastic Anisotropy: Effects Of Fiber Alignmenmentioning
confidence: 85%
“…1 C-E). Furthermore, this highly stretchable helix scaffold exhibits a strong nonlinear elasticity in the form of strain stiffening, which is widely observed in biopolymer networks and is thought to be of importance for tissue mechanical functions (36,46). The deformation process includes original separation of the adjacent coils and gradual unwinding of the coils until the fiber is free of it.…”
Section: Resultsmentioning
confidence: 99%
“…This reference state does not account for irreversible, inelastic deformations of the matrix, which may occur due to ECM remodeling or deposition. In future work, complementary measurements using optical tweezers 20,23 or direct imaging of fibers 18 could also be incorporated to address how multicellular clusters are affected by changes in the local stiffness of the surrounding matrix. Our classification of multicellular cluster mechanophenotype directly accounts for local spatial heterogeneity in the local 3D matrix deformation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Early TFM studies measured cell-cell and cell-matrix interactions of multicellular epithelial clusters on planar 2D substrates [8][9][10][11][12][13] . More recently, TFM has been extended to 3D hydrogels, but has primarily focused on individual cells [14][15][16][17][18][19][20][21][22][23][24] . Notably, epithelial cell lines exhibit more isotropic, spatially uniform tractions, while mesenchymal cell lines exhibit highly anisotropic tractions localized at the leading and trailing edge 14-16, 18, 20, 22, 23 .…”
Section: Introductionmentioning
confidence: 99%